EFFECT OF SIMULATION-BASED SPLINTING TRAINING ONKNOWLEDGE AND SKILLS OF DESTANA VOLUNTEERS: A PRE–POSTEXPERIMENTAL STUDY - Yeni Nur Rahmayanti; Fadma Aji Pramudita; Christiana Arin Proborini; Pipi Anonyma (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
A disaster is an event or series of events that threaten and harm people's lives,caused by natural factors, non-natural factors, or human activity, resulting inmaterial losses, loss of life, environmental damage, and psychologicalimpacts. Matesih District has many steep slopes and experiences heavyrainfall. This situation resulted in extensive erosion, soil weathering, andlandslides. One of the disasters that once struck Matesih was a landslide thatresulted in several people suffering minor injuries. Injuries experienced byresidents are usually related to the musculoskeletal system. This study aims toevaluate the impact of splinting training using simulation methods on theunderstanding and splinting skills of Destana volunteers in dealing withdisasters. The methodology used in this study is a quantitative research typewith a quasi-experimental design. There were 27 respondents who became thesample of this study, obtained through the Total Sampling Technique. Datawere analyzed using the Wilcoxon Test. The results of the Wilcoxon Testshowed a p-value of 0.000. This indicates the effect of splinting training usingsimulation methods on the understanding and splinting skills of Destanavolunteers in dealing with disasters in Girilayu Village, Karanganyar. Fromthese results, it can be concluded that splinting training using simulationmethods can improve the understanding and skills of splinting, so thatrespondents are more active in participating in the training and candisseminate the splinting skills they have learned.